Tokunagaia Sæther from China (Diptera: Chironomidae: Orthocladiinae) - Liu, Yuedan; Wang, Xinhu (Zootaxa, 2006)
The Chinese species of the orthoclad genus Tokunagaia Sæther are reviewed. Five new species, T. fasciata, T. quadrulata, T. spinosa, T. subulata, and T. unicentrata, are described and figured as males. The generic diagnosis is emended, and a key to the males of the Chinese species is provided.